COMPREHENSIVE APPROACH TO TREATMENT OF EXOGENOUS- CONSTITUTIONAL OBESITY IN CHILDREN - Yu.V. , Vladimirova; V.A, Zhirnov; O.V., Sazonova; M.Yu., Gavryushin; D.O., Gorbachyov (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, we presented a new tactic for managing children with exogenous-constitutional obesity against the background of leptin resistance. Body weight in children with and without leptin resistance did not differ statistically, but the degree of reduction in the 1 to 3 course of therapy was more expressed in children in the comparison group, without leptin resistance. So in the comparison group after the 1st course, the weight decreased by 2.27±0.78 kg, and in the main group - by 1.63±0.56 kg (p<0.001); after the second course of therapy, these values (weight reduction) were 4.40±1.43 kg and 3.28±1.10 kg (p<0.001); and finally after the last 3 courses - 6.60±2.14 and 4.91±1.64 (p<0.001).Signs of leptin resistance in children against the background of TMS became less noticeable and most children after 2 months noted a decrease or even absence of the majority, in contrast to children whose parents did not want to try to correct the child’s condition with TMS. Therefore, it is very important that a year after therapy in children who passed 3 courses of TMS, the trend remained: 95% of children continued to lose weight and only two people (4.8%) increased their weight. And in children receiving standard therapy, the vast majority (97.5%) returned to their original weight level or even increased slightly. This scheme of complex therapy will improve the quality of life of children in this category significantly.